ESTABLISHING REGIONAL ANTI-FRAUD OFFICE TO TACKLE FINANCIAL CRIME IN ASEAN - Reza Haidar Kamal (Asia Pacific Fraud Journal, 2017)
Corruption is still becoming hot issue around the world. Each country has its own way to combat corruption starting from the scope of national, regional to international cooperation to fight against this issue. Indonesia also has several strategies to eradicate corruption which are getting better from time to time. According to Transparency International (TI), as a member of regional organization, ASEAN, Indonesia is still ranked fourth,in Corruption Perception Index (CPI),out of tenmember countries. But the rank-range of ASEAN member countries is too far from one country to another, unlike European Union. Three member countries of European Union stand are on the top three of 168 countries. Besides having anti-corruption institution in each member country, European Union also has anti-fraud office, called OLAF, to tackle financial crime at regional level. Therefore, it is necessary for ASEAN to establish an institution that aims to combat corruption at regional level of ASEAN, just like the European Union’s OLAF, which has a mandate to detect, investigate and stop fraud related to EU’s funds.